PERKEMBANGAN PENDIDIKAN ISLAM DI SPANYOL - Adawiyah, Robiatul (e-Journal STAI Muhammadiyah Tulungagung, 2015)
Islamic presence in Spain has brought tremendous change, especially in social and science and culture. The development of Spanish civilization Islam is formed not just by the touch of the tradition of Arab-Islamic culture multicultural society is what ultimately bound together and form a high Islamic culture at that time. The development of science is also not out of tolerance and friendship offered Islam to the indigenous population that is resident Andalusia or Spain. Traversed a long history of Muslims in Spain it can be divided into six periods, but in this paper is defined only up to the third period, this period lasts from government Abd al-Rahman III title